FRI0482 Causes of death in connective tissue disease (CTD'S) and vasculitides; data from the norwegian connective tissue diseases and vasculitis registry (NOSVAR). (12th June 2018) - Garen, T.; Lerang, K.; Andersson, H.; Midtvedt, Ø.; Kilian, K.; Reister, S.; Gunnarsson, R.; Gudbrandsson, B.; Molberg, Ø.; Palm, Ø.
Abstract : Background: Mortality as an outcome of disease's severity and causes of death can give extended insight into the nature of each specific diagnose and highlight distinct needs for monitoring. In connective tissue diseases (CTD) and systemic vasculitides, mortality and causes of death have been studied within most single diseases, but with heterogeneity of the studies and widely varying results. Studies applying similar methods across the diagnoses are lacking. Consequently, it is difficult to compare causes of death between the different diagnoses. 1 Objectives: To identify the causes of death within different CTDs and systemic vasculitides. Methods: We performed a prospective, observational, controlled study between 1999 and 2017 of adult patients (at least 18 years of age) with diagnosis of CTD or vasculitides. All patients were included in the Norwegian connective tissue disease and vasculitis Registry (NOSVAR). In total, 2140 patients were diagnosed and followed up until death or study end by April 31th 2017. To avoid bias by selection, we included only incident cases, excluding patients with diagnoses set prior to 1999. Moreover, cases with a disease course not consistent with the initial diagnoses were excluded. Causes of death were identified by linking NOSVAR to the Norwegian Causes of Death Registry and by reviewing hospital charts. We divided the causes of death into the main groups of cardiovascular diseases (CVD), neoplasms, chronic respiratory disease (CRD), infections and other (gastrointestinal, renal insufficiency and trauma. To compare causes of death to the general population we used data from WHO Mortality Database, Causes of death. 2 Results: During a mean (SD) follow-up time of 9.2 years (4.7), 279 patients (13%) deceased. The major causes of death were, in descending order of frequency; CVD (27%), neoplasms (25%), CRD (16%), infections (11%), gastrointestinal manifestations (4%), renal insufficiency (2%). Data from the general population, adjusted for age and gender, showed that deaths by CVD, CRD and infections were more prevalent among the patients. 2 The leading causes of death are shown in figure 1. In Takayasu arteritis and lSSc, CVD was the most frequent cause of death; (56%) and (41%), respectively. More than half of the patients (53%) with antisynthetase syndrome died of CRD. Those with dematomyositis died most frequently of neoplasms (50%). Conclusions: Compared to general population, patients with CTD and vasculitidis died more often of CVD, CRD and infections. CVD as a cause of death was most prevalent in patients with Takayasu arteritis, giant cell arteritis and systemic sclerosis, while neoplasm was the major cause of death in dermatomyositis. In antisynthetase syndrome, both CRD was the major causes of death. The study gives the clinician valuable information on how to monitoring the different CTDs and vasculitidis regarding serious outcome. References: [1] Toledano E, Candelas G, Rosales Z, Martinez Prada C, Leon L, Abasolo L, et al. A meta-analysis of mortality in rheumatic diseases. Reumatologia clinical2012;8(6):334–41. [2] University of Washington, Causes of Death (COD) visualization VizHub. https:/vizhub.healthdata.org/cod/University of Washington;2017 [updated 2017cited2017]. Disclosure of Interest: None declared